Hope, Choice and the Improvable Self: A Critical Analysis of ‘New Recovery’ in Australia - Fomiatti, Renae Dorothy (Curtin University, 2017)
Drawing on science and technology studies, this thesis analyses how ‘new recovery’ is enacted in Australian alcohol and other drug policy, psychological science and treatment, and the extent to which authoritative enactments of recovery inform individuals’ lives. It argues that there exist important threads of continuity with older forms of recovery, most notably, in the neoliberal politics of responsibilisation, erasure of socio-political forces, and continuing stigmatisation of people who use drugs and their social relationships.